Early Origins of Adult Cancer Risk Among Men and Women: Influence of Childhood Misfortune?. (January 2018) - Kemp, Blakelee R.; Ferraro, Kenneth F.; Morton, Patricia M.; Mustillo, Sarah A.
Objective: To examine the effect of five childhood misfortune domains—parental behavior, socioeconomic status, infectious diseases, chronic diseases, and impairments—on all-site and selected site-specific cancer prevalence and all-site cancer incidence.Method: Panel data from the Health and Retirement Study (2004-2012) were used to investigate cancer risk among adults above the age of 50.Results: Risky parental behavior and impairment in childhood were associated with higher odds of all-site cancer prevalence, and childhood chronic disease was associated with prostate cancer, even after adjusting for adult health and socioeconomic factors. Moreover, having one infectious disease in childhood lowered the odds of colon cancer. Cancer trends varied by race and ethnicity, most notably, higher prostate cancer prevalence among Black men and lower all-site cancer among Hispanic adults.Discussion: These findings underscore the importance of examining multiple domains of misfortune because the type and amount of misfortune influence cancer risk in different ways.